Curcumin- and Piperine-loaded emulsomes as combinational treatment approach enhance the anticancer activity of Curcumin on HCT116 colorectal cancer model - Bolat, Zeynep Büşra; İşlek, Zeynep; Demir, Bilun Nas; Yılmaz, Elif Nur; Şahin, Fikrettin; Üçışık, Mehmet Hikmet (Frontiers in Bioengineering and Biotechnology, 2020)
Combination chemotherapy, administrating two chemotherapeutic agents concurrently, comes into prominence, as the heterogeneity or the level of the disease necessitates a collaborative action. Curcumin, isolated from turmeric, and piperine, isolated from black long pepper, are two dietary polyphenols studied for their intrinsic anti-cancer properties against various cancer types including colorectal cancer (CRC). Furthermore, piperine improves the therapeutic effect of curcumin. Addressing this mutual behavior, this study combines curcumin and piperine within emulsome nanoformulations. Curcumin- (CurcuEmulsomes) and piperine-loaded emulsomes (PiperineEmulsomes) have established a uniform, stable, spherical dispersion with average diameters of 184.21 and 248.76 nm, respectively. The solid tripalmitin inner core achieved encapsulation capacities of up to 0.10 mg/ml curcumin and 0.09 mg/ml piperine content. While piperine treatment alone - in its both free and emulsome forms - showed no inhibition in the proliferation of HCT116 cells in vitro, its presence as the second drug agent enhanced curcumin's effect. Combination of 7 mu M PiperineEmulsome and 25 mu M CurcuEmulsome concentrations was found to be most effective with an inhibition of cell proliferation of about 50% viability. Cell cycle arrest at G2/M phase and induced apoptosis verified the improved anti-cancer characteristics of the therapy. While CurcuEmulsomes achieved a fourfold increase in Caspase 3 level, combination of treatment with PiperineEulsomes achieved a sixfold increase in the level of this apoptotic marker. Combinational treatment of HCT116 cells with CurcuEmulsomes and PiperineEmulsomes improved the anticancer activity of the compounds and highlighted the potential of the approach for further in vivo studies.
Keywords: Curcumin; Piperine; Emulsome; Colorectal Cancer; Combination Chemotherapy